Assessment of community - based monitoring under NRHM in Nainital district of Uttarakhand - Kumar, S; Jha, S K; Rawat, CMS; Awasthi, S; Semwal, V; Bano, M (Indian Journal of Community Health, 2013)
Background: The government of India started the Community-Based Monitoring (CBM) under National Rural Health Mission (NRHM) which allow the community and its representatives to directly give feedback about the functioning of public health services. Uttarakhand was the 10th state where CBM system under NRHM implemented in 2010 in all 13 districts as pilot project. Objective: To assess the composition and training of Community Monitoring Groups (CMGs) at sub-centre and block level, the capability of the CMG to prepare the report card at sub-centre and facility score card at PHC and to study the improvement in quantitative aspects of health services in study areas. Methodology: This community based prospective study was carried out in two selected Haldwani and Bhimtal blocks of Nainital district. The period of study was from July 2011 to June 2013. Multi-stage random sample design was adopted to select 54 CMG members. Results: About 91% CMG members belong to General Category. Out of 54 CMG members, majority 45(83.3%) had received training and among them 80% did not have clarity about training guideline. The activities of preparing Report cards, Facility score cards and conducting Jan-Sunwais were done once in a year. Concurrent reductions in yellow (partially satisfactory) and red (bad) rating of series were not seen in 2011-12 to 2012-13 at all centres. Conclusion: The composition and training of the CMGs at all sub-centres and at PHCs were not as per guidelines of NRHM. The activities of preparing the Report card, the Facility score card and conducting Jan-sunwais were not done as per guidelines by NRHM. Majority of sub-centre indicators scored yellow colour and only few scored green.